A decomposition and decoupling analysis of carbon dioxide emissions from electricity generation: Evidence from the EU-27 and the UK - Karmellos, Marios; Kosmadakis, V.; Dimas, Petros; Tsakanikas, Aggelos; Fylaktos, Nestor; Taliotis, Constantinos; Zachariadis, Theodoros (My University, 2021)
In this paper the driving factors of carbon dioxide emissions from electricity generation in the European Union are examined for the years 2000–2018, separated into three time periods using decomposition analysis, and particularly LMDI-I. Seven driving factors are examined, namely the economic activity effect, the population effect, the electricity intensity effect, the electricity trade effect, the energy intensity effect, the generation structure effect, and the emissions factor effect. The results showed that the main driving factor leading to increased carbon dioxide emissions is the economic activity effect counterbalanced mainly by the contribution of the generation structure effect. Moreover, a decoupling analysis between economic growth and carbon dioxide emissions was carried out aiming to identify the state of each country for each period. In the third examined period (2013–2018) most countries in the EU-27 are in a state of strong decoupling.
Keywords: CO2 emissions; Decomposition model; Decoupling model; Electricity sector